KEABSAHAN POLIS ASURANSI ATAS KLAUSULA BAKU PADA PERJANJIAN ASURANSI DI PT. AXA MANDIRI CABANG KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Insurance is an agreement, with which an insurer ties himself to an insured by receiving a premiumto provide compensation for a loss, damage, or loss of expected benefits that he might suffer because of anuncertain event. The required insurance agreement is written in a written form called the policy. Insurancepolicies contain agreement clauses, both standard and non-standard. To find out about this issue, thestandard agreement is regulated in Law Number 8 of 1992 concerning Consumer Protection, whileinsurance is regulated in Law Number 40 of 2014 concerning Insurance. This is to provide legal protectionfor policyholders for their rights and for business actors to provide the obligations of business actors asinsurance companies with the applicable rules.This type of research can be classified in the type of research that sosiological, because in this studythe authors directly conduct research at the location or place of study in order to provide a complete andclear picture of the problem under study. The research was conducted at PT. Axa Mandiri Pekanbaru CityBranch, while the population and the sample are all parties related to the problems axamined in this study,the source of the date used, primary,secondary, and tertiary, then the collection in this study by interviewand study documents.It can be said that the insurance policy has been provided in advance by the guarantor. Theinsurance policy holder as the party that binds themselves to the insurance company through an insuranceagreement gets legal protection in various laws and regulations such as in Law Number 2 of 2011concerning the Financial Services Authority, Law Number 40 of 2014 concerning Insurance, and in theFinancial Services Authority Regulation Number 1 / POJK.07 / 2013 concerning Financial Services SectorConsumer Protection. Given that insurance policy holders are generally individual or individual and not afew whose economic conditions are weak dealing with insurance companies, then a number of laws andregulations are more concerned and legal protection for insurance policy holders than the possibility oropportunity of violation of law by insurance companies. The legal consequences of violations of insuranceagreements will be faced by violators, which in this case will result in lawsuits that can be resolved throughcourt lines or through arbitration and alternative dispute resolution.Keywords: Insurance – Policy – Standard Clause